New inductive proximity sensor platform for precise localization of small colorectal tumors - Bintintan, Vasile; Calborean, Adrian; Mocan, Mihaela; Macavei, Sergiu; Cordoș, Adrian; Ciuce, Catalin; Bințințan, Adriana; Chira, Romeo; Nagy, Georgiana; Surlin, Valeriu; Timofte, Dan; Nickel, Felix; et al. (Materials science & engineering. C, Materials for biological applications, 2020)
Location of small gastric or colorectal tumors during a laparoscopic procedure is often imprecise and can be misleading. There is a real need for a compatible and straightforward tool that can be used intraoperatively to help the surgeon in this regard. We emphasize in the present work on the fabrication of a new and innovative inductive proximity switch architecture, fully compatible with laparoscopic surgery and with direct application in precise localisation of bowel tumors. An electromagnetic detection probe optimized for laparoscopic surgery and preconditioned for sterilisation was designed and constructed. Various metallic markers designed to be attached to the gastrointestinal mucosa were used for detection by the probe, from standard endoscopic and laparoscopic haemostatic clips to other custom made tags. Experiments were performed in dry and wet-lab experimental laboratory environment using ex-vivo segments of calf's small bowel and colonic surgical specimens from human patients. The dry-lab detection range varied considerably depending on the metallic component of the tags, from 0.5mm for the endoscopic hemostatic clip to 3.5mm for the 0.9mm thickness stainless-steel custom tags. The latter was actually detectable from the serosal side of the fresh colonic surgical specimens in 85% of the attempts if the scanned area was less than 150cm2 and less than 2mm of fat was interposed between the probe and the bowel. The newly designed system has the potential to discover metallic tags attached to the bowel mucosa for precise intraoperative laparoscopic location of digestive tumors. Further work is in progress to increase the sensitivity and detection range of the system in order to make it fully compatible with the clinical use.